PROSES PRODUKSI INJECTION PHYLON - Purnomo, Ade; Rachmat , Asep (Universitas Majalengka, 2024)
ABSTRACT The shoe industry in Indonesia has great potential to compete in the global market, producing high-quality products that are in demand by international consumers. In 2018, the industry produced 1.41 billion pairs of shoes, accounting for 4.6% of the world's shoe needs, making Indonesia the fourth largest shoe producer in the world. However, challenges remain, including the Termination of Employment Relationships which raises concerns among the public and investors. The government seeks to provide positive information about investment and labor absorption. One of the innovations in this industry is the use of a phylon injection machine, which is able to produce the bottom of the shoe with high precision and efficiency. This production process involves advanced technology and the use of special materials such as phylon, which has advantages in elasticity, durability, and comfort. This research method includes observation, literature study, field practice, and data analysis. The results of the study show that the use of a phylon injection machine can improve the production efficiency and quality of shoe products. The conclusion of this study is that innovation and technology in the Indonesian shoe industry can strengthen global competitiveness and make a positive contribution to the economy.